The Effectiveness of Applying Reinforcement Techniques to Increase Interest in Reading the Qur'an among UIN Malang Students - Faza Tsaniya Hurin; Thalita Nur Shobiroh; Muhammad Jamaluddin (Journal of Innovative and Creativity (Joecy), 2026)
Interest in reading the Qur'an among university students has become a growing concern in Indonesian Islamic higher education, as national data indicates that a large proportion of Muslim students have not yet attained adequate Qur'anic literacy. The study purpose was to examine the effectiveness of applying reinforcement techniques in increasing interest in reading the Qur'an among students of UIN Maulana Malik Ibrahim Malang. Reinforcement techniques, grounded in Skinner's operant conditioning theory, are proposed as a behavioral intervention strategy to address this challenge. Materials and methods. This study employed a quantitative approach with a one-group pretest-posttest experimental design. The sample consisted of 19 active students of UIN Maulana Malik Ibrahim Malang, selected through simple random sampling. The primary instrument was a Qur'anic Reading Interest Scale developed based on four dimensions proposed by Slameto (2010): attention, positive feeling, attraction, and individual involvement, measured using a 4-point Likert scale. A monitoring sheet was also used to track reading consistency throughout the intervention. Data were analyzed using the Wilcoxon Signed Ranks Test with IBM SPSS Statistics. Results. The Wilcoxon Signed Ranks Test yielded a Z-value of -3.803 with a significance value of 0.000 (p < 0.05). All 19 participants showed an increase in Qur'anic reading interest scores from pretest to posttest, with no subjects experiencing a decrease or stagnation, indicating a highly consistent pattern of improvement across all individuals. Conclusions. The application of reinforcement techniques is significantly effective in increasing interest in reading the Qur'an among UIN Maulana Malik Ibrahim Malang students. Improvements were observed across all four dimensions of reading interest, suggesting a holistic and internalized development of students' psychological engagement with Qur'anic reading. These findings support the use of reinforcement techniques as a practical behavioral intervention strategy in Islamic counseling and Qur'anic education at the higher education level.